Cornici di tortura Lo scandalo di Abu Ghraib come rituale mediatizzato tra fotogiornalismo e arte contemporanea (Altre Modernità, 2010)
This paper deals with the scandal of Abu Ghraib. The diffusion of the torture photographs is analyzed as a peculiar form of mediatized ritual, which has cristallized them in the public memory and performatively activated a number of practices of creative re-contextualization and symbolic re-articulation. In particular, the paper problematizes a wide range of forms of artistic representations of the torture photographs, according to three main analytical dimensions: inter-iconic translation, authorial intentions, degree of institutionalization.